1989
DOI: 10.1084/jem.169.5.1669
|View full text |Cite
|
Sign up to set email alerts
|

T cell-mediated inhibition of the transfer of autoimmune diabetes in NOD mice.

Abstract: The nonobese diabetic (NOD)' mouse provides a relevant model for insulindependent diabetes mellitus (IDDM). Spontaneous IDDM is usually observed after 12 wk of age and largely predominates in females (1). The role of autoimmune phenomena in the destruction of islet (3 cells in this model is indicated by islet infiltration by mononuclear cells, mainly T lymphocytes (2, 3), by prevention ofIDDM by neonatal thymectomy (4), and by in vivo treatment with cyclosporine A (5), anti-CD4 + (6, 7), or anti-I-A mAbs (8). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
148
1
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(161 citation statements)
references
References 20 publications
10
148
1
2
Order By: Relevance
“…Interestingly, the number of autoreactive precursor T cells is similar between males and females but male lymphocytes are functionally less aggressive [36]. Furthermore, male NOD mice are more sensitive to the inhibitory activity of regulatory T cells than females [37]. The incidence of diabetes in male transgenic 8.3-NOD mice is lower than in females; however, similar numbers of autoreactive T cells populate their lymphoid organs [8].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the number of autoreactive precursor T cells is similar between males and females but male lymphocytes are functionally less aggressive [36]. Furthermore, male NOD mice are more sensitive to the inhibitory activity of regulatory T cells than females [37]. The incidence of diabetes in male transgenic 8.3-NOD mice is lower than in females; however, similar numbers of autoreactive T cells populate their lymphoid organs [8].…”
Section: Discussionmentioning
confidence: 99%
“…The absence of Th2 cells within the islet cell infiltrate was supported by experiments in which no IL-4-secreting T cells were detected within the islet infiltrate upon transfer of spleen cells from either 8-week-old or diabetic NOD mice into conventional recipients. Suppressive CD4 T cells were detected in 8-week-old NOD spleens [6,34] Spleen CD4 þ or CD8 þ T cells were purified from the spleens of diabetic female NOD mice. CD4-enriched T cells were composed of 73% CD4 þ /CD8 ¹ and 0·1% CD8 þ /CD4 ¹ cells; CD8-enriched T cells were composed of 52% CD8 þ /CD4 ¹ and 0·01% CD4 þ /CD8 ¹ cells.…”
Section: Discussionmentioning
confidence: 99%
“…NOD mice only develop diabetes at 3 or 4 months of age, however, insulitis occurs long before the clinical onset of diabetes [18]. Disease transfer into irradiated recipients by spleen cells from diabetic NOD mice is prevented by CD4 + T cells from young pre-diabetic NOD mice were co-transferred with diabetogenic T cells [19]. Recent data have indicated that this protective effect is confined to a CD4 + CD25 + CD62L + Treg subset [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The B chain peptide, B:9-23, has been suggested to be a primary autoantigenic epitope in the pathogenesis of type 1 diabetes in NOD mice [4,5]. However, of interest, immunization of NOD mice with exogenous B: [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] peptide prevents diabetes [6].…”
Section: Introductionmentioning
confidence: 99%